Kepemimpinan Kepala Madrasah dalam Meningkatkan Motivasi Kinerja Guru di Madrasah Ibtidaiyah Attahdzibiyah Babat - Sinta Mauludya; Ahmad Faizin; Ahmad Thohirin; Sinta Mauludya; Ahmad Faizin; Ahmad Thohirin (Jurnal Riset Madrasah Ibtidaiyah, 2026)
The leadership of madrasah principals plays a strategic role in enhancing teacher performance motivation in Madrasah Ibtidaiyah. This study aims to analyze the leadership practices of the madrasah principal in fostering teacher work motivation at MI Attahdzibiyah Babat, Lamongan Regency. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation involving the madrasah principal and teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that leadership is implemented through exemplary behavior, effective communication, teacher empowerment, and support for professional development. These practices create a conducive work climate that positively impacts teachers’ discipline, responsibility, commitment, and initiative in the learning process. Theoretically, the findings confirm that adaptive and participatory leadership oriented toward teacher professional development is a key factor in strengthening sustainable teacher performance motivation.